A novel c.1468 G > A GRN mutation causes frontotemporal dementia in a Chinese Han family - Mingrong Xia; Chenhao Gao; Junkui Shang; Dan Li; Ali Yang; Weizhou Zang; Jiewen Zhang (European Journal of Medical Research)
Abstract Background/purpose GRN mutations act as causative factors in patients with FTD clinical phenotype or FTD pathology and exhibit high clinical heterogeneity. The discovery of these mutations and the analysis of their associations with resembling Alzheimer’s disease should be critical to understand the pathogenesis of FTD. Methods Clinical analysis, neuroimaging, target region capture and high-throughput sequencing were performed in a family of 3 generations. The underlying Alzheimer’s pathology was evaluated by using biomarker evidence obtained from cerebrospinal fluid (CSF) amyloid testing, 18F-florbetapir (AV-45) PET imaging and FDG18-positron emission tomography imaging. Results Through target region capture and high-throughput sequencing, a three-generation family was able to identify a heterozygous G to A point mutation at position 490 (c.1468)G > A, which led to a valine to methionine substitution (V490M) at exon 12. This unique missense mutation was found at codon 1468. Eight members of the proband's family—two sisters and the proband himself—had the mutation found by Sanger sequencing. Interestingly, biomarker tests for amyloid in the proband's cerebrospinal fluid (CSF) indicated pathology consistent with Alzheimer's disease (AD). The mutation was expected to have a high likelihood of being pathogenic. Conclusions We firstly reported a novel mutation in the GRN gene at codon 490 (V490M) in exon 12 in a China FTD family. The CSF biomarker alterations of the proband revealed a reduction in Aβ42 and the Aβ42/Aβ40 ratio. The analysis of mutation might support the role of GRN in patients with FTD and contribute to the discovery of a new pathological mechanism underlying the disease.